2017
DOI: 10.1111/jace.15249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium on setting mechanism of metakaolin‐based geopolymer

Abstract: Geopolymer setting is seen to be substantially accelerated by addition of calcium and the objective of this study was to determine the mechanism for this effect by examining metakaolin geopolymers with and without calcium. Solid‐state 27Al NMR tests were used to examine the dissolution extent both qualitatively and quantitatively. Solid‐state 29Si NMR tests were conducted to determine the amount and structure of each phase. Prior to the quantitative tests, chemical extractions were used to facilitate assignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 50 publications
6
62
0
Order By: Relevance
“…This indicates that Ca(OH) 2 was consumed during the alkali-activation reactions. In line with the obtained results, Chen et al [4] observed that adding calcium to metakaolin geopolymers enhanced the rate and extent of MK dissolution. The higher dissolution rates of the precursor increased the Al concentration in the solution as Al tends to dissolve faster than Si [4].…”
Section: Role Of Calcium In the Kinetics Of The Processsupporting
confidence: 75%
See 3 more Smart Citations
“…This indicates that Ca(OH) 2 was consumed during the alkali-activation reactions. In line with the obtained results, Chen et al [4] observed that adding calcium to metakaolin geopolymers enhanced the rate and extent of MK dissolution. The higher dissolution rates of the precursor increased the Al concentration in the solution as Al tends to dissolve faster than Si [4].…”
Section: Role Of Calcium In the Kinetics Of The Processsupporting
confidence: 75%
“…In line with the obtained results, Chen et al [4] observed that adding calcium to metakaolin geopolymers enhanced the rate and extent of MK dissolution. The higher dissolution rates of the precursor increased the Al concentration in the solution as Al tends to dissolve faster than Si [4]. As explained by Ranjbar et al [7], the bigger amounts of Al(OH) 4 − species available for condensation at early ages improve the condensation rate between silicate and aluminate species, rather than only between silicate species.…”
Section: Role Of Calcium In the Kinetics Of The Processsupporting
confidence: 75%
See 2 more Smart Citations
“…The alkali‐activated material can be mainly composed of the calcium aluminosilicate hydrate (CASH) or the sodium aluminosilicate hydrate (NASH) based on the calcium content. Currently, it is generally considered that the CASH gel has a layer structure which is similar to the calcium silicate hydrate (CSH) gel and the NASH gel possess the 3D network structure formed by aluminate and silicate tetrahedrons linked with shared oxygen atoms . It has also been reported that the aluminum normally can be introduced into the structure of CSH by partially substituting the silicate tetrahedrons at the bridging sites to form CASH gel, but the detailed structure examination at the atomic scale for the CASH gel is still limited.…”
Section: Introductionmentioning
confidence: 99%